Self-limited growth of triangular PtO2 nanoclusters on the Pt(111) surface - SHVETS, IGOR (My University, 2010)
The high temperature oxidation of the Pt(111) surface by molecular oxygen has been studied using scanning tunnelling microscopy (STM) and low-energy electron diffraction (LEED). Results indicate a self-limited growth of well-ordered PtO2 nanoclusters which have an O-Pt-O trilayer structure. Each nanocluster has a triangular shape and nucleates at the Pt(111) surface step edge due to mobility of Pt atoms. The triangular PtO2 nanoislands on the upper and lower Pt(111) terraces represent two mirror domains with the mirror plane perpendicular to the substrate and aligned along the [1-10] direction of the latter. LEED data obtained from the nanostructured PtO2/Pt(111) surface show a characteristic (2?2) pattern. Different oxidation conditions lead to the formation of chemisorbed oxygen on the Pt(111) surface alongside PtO2 nanoclusters. Oxygen adsorbs on the surface forming variety of structures which result in (3?3), (5?5) and (7?7) LEED patterns.
PUBLISHED
Keywords: Self-limited growth; atomic oxygen; platinum; sites; adsorption; oxide; high coverage structures; co oxidation; Nanoscience & Materials